Pension Reform Preferences in Germany: Does Information Matter? - Jana Schuetz; Silke Uebelmesser; Ronja Baginski; Carmela Aprea (Center for Economic Studies and ifo Institute (CESifo), 2022)
Demographic change has an impact on pay-as-you-go pension systems. To maintain their financial sustainability, reforms are necessary, but often lack public support. Based on representative survey data from Germany, we conduct a survey experiment which allows investigating whether salience of or information about demographic change enhances preferences towards reforms in general as well as towards specific reform measures. We find that salience and information provision significantly increase the perceived reform necessity. Furthermore, salience increases preferences for an increase of the retirement age over other reform measures, while information provision reduces preferences for tax subsidies. In addition, we highlight the impact of prior beliefs on the treatment effects. As the salience and the information treatments barely differ, we conclude that it is not the information about the demographic change, which matters. Rather, being made aware of the challenges of the pension system impacts reform preferences.
Keywords: H55; J26; C90; 330; pension reform preference; survey experiment; demographic change; information provision